Dynamic changes in the tumor microenvironment under the effect of estradiol as a diagnostic tool and target for targeted cancer therapy - A. I. Stukan; A. Yu. Goryainova; A. A. Meshcheryakov; V. A. Porkhanov; R. A. Murashko; S. V. Sharov; V. N. Bodnya (Бюллетень сибирской медицины)
Activation of the estrogen receptor-α (ER-α) signaling pathway is a significant factor in the initiation of carcinogenesis in various types of tumors due to the genomic and non-genomic effects of estradiol in cancer cells. However, data on the expression of ER-α and aromatase on stromal and immune cells in the tumor microenvironment (TME) point to an additional mechanism by which estrogens increase tumor malignancy. There is growing evidence that TME can affect tumor immunity by increasing the immune response or reducing immunoreactivity.The important role of estrogen and the estrogen receptor signaling pathway in the response of the tumor microenvironment in cancer of various localizations, not only classical hormone-dependent cancers, has been proven. However, the clinical effectiveness of blocking the effect of estrogen on tumor growth has been primarily shown in cancer of the female reproductive system. At the same time, data on the significant role of TME in the development of endocrinotherapy resistance in breast cancer treatment are of great interest.Despite the possibilities of standard therapy, a more in-depth study on the role of various TME components in cancer evolution, creation of a micrometastatic niche, as well as in the response to therapy may result in development of new strategies for cancer treatment. It is also necessary to study the possibilities of overcoming the immunosuppressive effect of the estrogen receptor signaling pathway on TME in order to increase the survival rates in patients with hormone-dependent cancers, particularly, breast cancer.